Handout Pembelajaran IPA Biologi SMP Berbasis Riset Morfologi Akar Tumbuhan Lahan Gambut Pasca Kebakaran - Fauziah, Yuslim; Syafii, Wan; Firdaus, L.N.; Zainun, Zainun (Indonesian Biology Teachers, 2018)
Abstract. Peatland fires have a negative impact on plant life. This study aims to produce Class VIII Biology Science Learning Handout SMP by utilizing the results of a study on the morphological characteristics of the roots of peatland plants after the fire. To achieve these objectives, a survey was conducted in Rimba Panjang Village, Kampar District, Riau Province in February-October 2017. Quadratic methods and sampling techniques were purposively applied to the gradient of fire incidents in 2009, 2013, 2014, 2015, 2016 and 2017. The parameters observed were root plant morphology of dominant sapling level (root root and lateral root). Data were analyzed descriptively-qualitative. Sapling strata vegetation research results have 6 dominant species namely Evodia roxburghiana, Acacia mangium, Ilex cymosa, Eugenia pelyta, Macaranga triloba and Cratoxylon arborescens. The types of fire-retardant post-fires are Cratoxylon arborescens and Acacia mangium which have good morphological characteristics Roots are good with root systems deep within the soil and have considerable amounts of lateral roots. This study reveals that the root morphological characteristics of dominant plants have deep root system and considerable amount of lateral roots. The handout could be implemented to enrich the repertoire of biology science in junior high school. Keywords: Biology Science Learning Handout, Post-fire peatland, Root Morphology, Senior High School.